2014
DOI: 10.1038/clpt.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2D6 Polymorphisms on Clinical Efficacy and Tolerability of Metoprolol Tartrate

Abstract: Metoprolol is a selective β-1 adrenergic receptor blocker that undergoes extensive metabolism by the polymorphic enzyme, CYP2D6. Our objective was to investigate the influence of CYP2D6 polymorphisms on efficacy and tolerability of metoprolol tartrate. 281 study participants with uncomplicated hypertension received 50 mg of metoprolol twice daily followed by response guided titration to 100 mg twice daily. Phenotypes were assigned based on results of CYP2D6 genotyping and copy number variation assays. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 24 publications
1
100
2
Order By: Relevance
“…Indeed, the emphasis of this review has been on drug efficacy and agent selection. However, there is significant evidence supporting variants predicting adverse events including the hyperuricemia of thiazide use 94 , bradycardia associated with β-blockers [5][6][7][8]95,96 , and ACEI-related cough 97 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the emphasis of this review has been on drug efficacy and agent selection. However, there is significant evidence supporting variants predicting adverse events including the hyperuricemia of thiazide use 94 , bradycardia associated with β-blockers [5][6][7][8]95,96 , and ACEI-related cough 97 .…”
Section: Methodsmentioning
confidence: 99%
“…However, a prospective, double-blind, longitudinal study of metoprolol use found significant differences in diastolic BP (DBP), QT interval, heart rate, and incidence of bradycardia 6,7 . As such, the Dutch pharmacogenomics working group (DPWG) has endorsed CYP2D6 screening with the use of metoprolol 8 .…”
Section: Metabolism Polymorphismsmentioning
confidence: 99%
“…Details regarding enrollment criteria have been previously published, and the studies are registered at clinicaltrials.gov (PEAR, NCT00246519; PEAR2, NCT01203852). 14,15 In both studies, male or female patients 17-65 years of age, of any race or ethnicity, with uncomplicated HTN were included. Study participants were excluded if they had complicated HTN, DM (or fasting blood glucose ‡ 126 mg/dL) or documented CVD (including history of angina pectoris, heart failure, cardiac pacemaker, myocardial infarction, stroke, etc.…”
Section: Pear Studiesmentioning
confidence: 99%
“…The PEAR-2 study was a multicenter sequential monotherapy clinical trial (clinicaltrials.gov identifier NCT01203852) 12 evaluating genetic determinants of BP response to metoprolol monotherapy and chlorthalidone monotherapy. Both PEAR-1 and PEAR-2 studies included individuals with mild to moderate essential hypertension.…”
Section: Methodsmentioning
confidence: 99%